R & D and productivity : the econometric evidence - Griliches, Zvi, 1930-1999 (National Bureau of Economic Research monograph., 1998)
Zvi Griliches, a world-renowned pioneer in the field of productivity growth, has compiled in a single volume his pathbreaking research on R & D and productivity. Griliches addresses the relationship between research and development (R & D) and productivity, one of the most complex yet vital issues in today's business world. Using econometric techniques, he establishes this connection and measures its magnitude for firm-, industry-, and economy-level data. Griliches began his studies of productivity growth during the 1950s, adding a variable of ""knowledge stock"" to traditional produc